The Effect of ACTN3 and VDR Polymorphisms on Skeletal Muscle Performance in Axial Spondyloarthropathies - Pimenta, Isabel; Mateus, Hugo; Rodrigues-Manica, Santiago; Pinheiro-Torres, Rita; Neto, Agna; Domingues, Lúcia; Lage Crespo, Carolina; Sardoo, Atlas; Machado, Pedro; Branco, Jaime C.; Silva, Susana N.; Pimentel-Santos, Fernando M. (Frontiers in Genetics, 2021)
Background: Spondyloarthritis (SpA) are the most common group of chronic inflammatory rheumatic diseases affecting about 1.5% of the adult Caucasian population. Low back pain is the most common symptom. The aetiopathogenesis of SpA is multifactorial, with well-known genetic and environmental contributions. Furthermore, muscle properties might also be involved in the pathophysiological process and these could be modulated by the genetic background. Alpha-actinin-3 (ACTN3) and Vitamin D receptor (VDR) genes are well-known genes related with muscle performance. Our aim was to analyse four SNPs of these genes and to evaluate their influence in axial SpA (axSpA) susceptibility, phenotype and muscle properties. Methods: We performed a pilot study based on case-control approach involving 56 participants: 28 axSpA patients and 28 healthy controls matched by age, gender and levels of physical activity. Clinical, epidemiological and muscle characterization data - muscle physical properties (stiffness, tone and elasticity), strength, mass, and performance, were collected. Two different muscles were considered for analysis, the Multifidus and Gastrocnemius. Four SNPs of ACTN3 (rs1815739) and VDR (rs2228570, rs731236 and rs7975232), were selected, analyzed and correlated with clinical, epidemiological and muscle characterization data. Results: In total, 51 individuals (27 axSpA patients and 24 matched controls) were eligible for further genetic analysis, 66.7% being male and with a mean age of 36 years. Muscle physical properties, muscle strength and muscle mass were similar in both groups; however, axSpA patients showed a decrease in muscle performance. None of the studied SNPs were associated with disease susceptibility/phenotype, muscle physical properties, muscle strength or muscle mass. However, ACTN3 rs1815739 and VDR rs2228570 were shown to be associated with muscle performance. Conclusion: Our results suggest an association between ACTN3 and VDR polymorphisms and muscle performance in axSpA.